Окремi фiзичнi фрiзаути дивних та недивних адронiв та проблема залишкової хiмiчної нерiвноваги дивностi в релятивiстських зiткненнях важких iонiв - Bugaev, K. A.; Oliinychenko, D. R.; Sagun, V. V.; Ivanytskyi, A. I.; Cleymans, J.; Mironchuk, E. S.; Nikonov, E. G.; Taranenko, A. V.; Zinovjev, G. M. (Publishing house "Academperiodika", 2019)
We present an elaborate version of the hadron resonance gas model with the combined treatment of separate chemical freeze-outs for strange and non-strange hadrons and with an additional ys factor which accounts for the remaining strange particle non-equilibration. Within the suggested approach, the parameters of two chemical freeze-outs are connected by the conservation laws of entropy, baryonic charge, third isospin projection, and strangeness. The developed model enables us to perform a high-quality fit of the hadron multiplicity ratios measured at AGS, SPS, and RHIC with X2/dof ≃ 0.93. A special attention is paid to a successful description of the Strangeness Horn. The well-known problem of selective suppression of Λ and Ξ hyperons is also discussed. The main result is that, for all collision energies, the ys factor is about 1 within the error bars, except for the center-of-mass collision energy 7.6 GeV, at which we find about 20% enhancement of strangeness. Also we confirm the existence of strong jumps in the pressure, temperature, and effective number of degrees of freedom at the stage of strange particle chemical freeze-out, when the center-of-mass collision energy changes from 4.3 to 4.9 GeV. We argue that these irregularities may signal about the quark-hadron phase transition.